PECULIARITIES OF EXPERIMENTAL VERIFICATION OF THE INTENDING MANAGERS-AGRARIANS' COMMUNICATIVE COMPETENCE FORMATION TECHNIQUE - Ольга Краєвська (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The peculiarities of testing the methods of managers-agrarians' communicative competence formation have been substantiated in this article, taking into account the specificity of such technique. The methods and means of experimental verification of the components of future managers-agrarians' communicative competence have been analyzed in this research. The author's methods of diagnosing the level of formation of the components of future managers-agrarians' communicative competence has been described. These methods include the following components: diagnosing motivation and value component, diagnosing cognitive and strategic component, and diagnosing activity and correction component. The connection between the experiment methods, the structure of future managers-agrarians' communicative competence and peculiarities of its formation methods has been studied in this article. There have benn described author's methods of future managers-agrarians' communicative competence formation, based on the development of the competence components, considering previously diagnosed flaws and problems of communicative training of specialists.